From Dust to Divinity: Christian Personhood, Resurrection, and the Metaphysics of Death - SAKTI, Paulus Nugraha (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
Christianity’s resurrection-centered anthropology offers a radical vision of personhood that transcends biological death. This paper examines how Christian theology constructs a metaphysics of persistent identity through its doctrines of bodily resurrection, the intermediate state, and the imago Dei. Drawing on scriptural exegesis (1 Corinthians 15; Job 19:25–27), patristic sources (Augustine, Gregory of Nyssa), and contemporary philosophical theology (N.T. Wright, Eleonore Stump), the study analyzes Christianity’s unique solution to the “problem of personal continuity” in death. It contrasts the resurrection paradigm with secular materialist views and transhumanist immortality projects, demonstrating how Christian eschatology preserves both corporeal and narrative identity. The paper then explores pastoral implications, showing how resurrection-based personhood shapes rituals of dying, grief practices, and bioethical decision-making in Christian communities. Ultimately, the argument reveals Christianity’s distinctive contribution to thanatology: a vision of death not as personal annihilation but as transformative passage within God’s sustaining grace.